Precision dosing of targeted anticancer drugs—challenges in the real world - Kim, Hannah Yejin; Martin, Jennifer H.; Mclachlan, Andrew J.; Boddy, Alan V. (Translational Cancer Research; Vol 6, Supplement 10 (December 14, 2017): Translational Cancer Research (Focused Issue: Precision Dosing of Targeted Anticancer Drugs), 2017)
Abstract: The prerequisites for the successful implementation of therapeutic drug monitoring (TDM) include high inter-subject variation, low inter-occasion variation, narrow therapeutic index and a strong link between plasma drug concentrations and clinical effects. The degree to which targeted anticancer drugs meet these criteria is not the only consideration in implementing precision dosing. Methodological, logistical, funding and cultural barriers also provide challenges to the successful implementation of approaches to individualised therapy. This review considers the barriers to the routine use of TDM, using examples from both conventional (cytotoxic) anticancer, but also considering more recent data and examples more relevant to chronic, oral administration of targeted therapies. Based on these examples and the associated principles for the implementation of precision dosing, proposals may be made for a more rational, real-world approach to the best use of precision medicines.